Asymptomatic Covid-19: A Model Kit - Luis Turabian, Jose (International Research in Medical and Health Sciences, 2021)
Actions on asymptomatic SARS-CoV-2 infections are a fundamental piece of a "model kit" against COVID-19. It has been claimed that up to 40% of infections can be asymptomatic. Without a doubt, the transmission of SARS-CoV-2 from people without symptoms contributes to the spread of the pandemic acting as a "silent driver." Presymptomatic and asymptomatic transmission significantly reduces the effectiveness of control measures that start with the onset of symptoms, such as isolation and follow-up of contacts. In a community transmission scenario, what is desired is to know is whether a patient is contagious. The antigen test is the most powerful tool we have to find out it. So, the focus of testing programs for SARS-CoV-2 should be expanded to include people who do not have COVID-19 symptoms. It is not clear whether the screenings performed so far have worked well, but it is possible that in the coming months the efficacy of the use of antigens for mass testing will improve. Even antigen tests can have an individual use; almost a home use. Having cheap, fast, and self-executing antigens, they may become mandatory for risky activities: traveling by plane, dining in a restaurant, or hanging out with a group of friends for a few days.